“You Don’t Belong in Hospital”: How Hospital-Based Dementia Stigma Shapes Health-Related Quality of Life - Alixe Ménard; Mackda Donkor; Sarah Fraser (Dementia, 2026)
Health-related quality of life reflects individuals’ perceptions of how a health condition affects their physical, psychological, and social functioning. Amid increasing pressures on primary care systems, people living with dementia are presenting more frequently to hospital settings. However, limited research has explored how hospital-based care, and the dementia stigma that may operate within it, shapes health-related quality of life for people living with dementia and their caregivers. This exploratory qualitative study involved semi-structured interviews with 15 participants, including people living with dementia and caregivers of individuals who had attended an emergency department or been hospitalized in Canada within the past two years. The interview guide was informed by the Wilson and Cleary Model of Health-related Quality of Life and intentionally avoided terms such as “stigma,” “bias,” or “discrimination” to reduce response priming. Data were analyzed using Fairclough’s critical discourse analysis and mapped to health-related quality of life factors (i.e., characteristics of the individual, biological and physiological factors, general health perceptions, etc.). Twelve caregivers (mean age 59.8 years, standard deviation = 9.7) and three people living with dementia (mean age 70.6 years, standard deviation = 11.8) participated between September and December 2025. Five interrelated discourses emerged: (1) characteristics of the individual: identity precedes clinical assessment; (2) biological and physiological factors: dementia disclosure as double-edged; (3) symptom and functional status: diagnostic overshadowing; (4) general health perceptions: equating dementia to futility; and (5) characteristics of the environment: structural barriers to recovery. Hospital-based discourses that implicitly or explicitly associate dementia with decline and therapeutic futility may contribute to stigma and negatively influence health-related quality of life for people living with dementia, while also intensifying caregiver distress. These findings underscore the need for stigma-reduction strategies in acute care settings that challenge therapeutic nihilism (i.e., inappropriately pessimistic view of patient outcomes) and promote person-centered, equitable hospital care.